The Research Of Studentsâ€™ Motor Ability In Archery Extracurricular - Arisman, Arisman; Agun Guntara, Roby (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
Â The purpose of this study was to determine the Motor Ability of Archery Extracurricular Students at Harapan Indonesia Elementary School. This research is motivated by the low basic movement ability of students so that it needs to be studied further. This ability is very necessary for the development of students because with the increasing number of students doing Multilateral Movement. then, the students' motor skills will also get better. This greatly affects the talents possessed by each student in achieving achievements, especially in the field of Archery. The type of research used is descriptive in describing certain conditions with a sample of 30 male students. The sampling technique was taken by purposive sampling, namely the sampling was based on certain considerations. The implementation was carried out at Harapan Indonesia Elementary School. Data were taken using Motor Ability Test with a range of 10-12 years. The data analysis technique uses descriptive statistics. The results of the analysis showed that the motor skills of students from 30 respondents were obtained in the "very good" category as many as 7 people or 23.33%, the "good" category as many as 9 people or 30.00%, the "moderate" category as many as 12 people or 40.00%, the "less" category as many as 2 people or 6.67%, while there is no â€œvery littleâ€ category.Key words: Motor Ability, Archery, Ektracurricular